Pengaruh Pengelolaan Unit-unit Usaha Pondok Terhadap Pembentukan Jiwa Wirausaha Santri (Studi Kasus Unit-unit Usaha Pondok Modern Darussalam Gontor Putri 2) - Andi Triyawan (University of Darussalam Gontor, 2016)
As an institution that expected to realize the civil society, Darussalam Gontor Modern Boarding school with the dynamics of community life, able to provide knowledge for all it’s graduated. In order to maintain and develop PMDG, and to fullfil the student needs. So that it build the business units and it managed by students and teachers. This is a spirit of Gontor Economy independence in funding and also a place for learning and practicing abaout entrepreneurship. The Aims of this study is to determine the effect of student cooperative management on the establishment of entrepreneurial spirit of students and what the activities that mostly give influence the entrepreneurial spirit, especially in Gontor for girls the second Campus. Actually by a few Student expected every learners can feel and do all activities in the Bussiness unit. By that model, spirit of Entrepreneurship can be applied in their live. The research method that used in this research is descriptive quantitative, that explain the existing phenomena through statistical calculations by using multiple regression analysis formula with the classical assumption test. The results of this research show that the influence of independent variables on the dependent variable as a whole is significant. Although in this study, independent variables (planning, organizing, implementation, monitoring and evaluation) are just the organizing stages that have the highest influence on the dependent variable (entrepreneurial spirit). This research is far from perfect and hope an advice and critics from the readers, may Allah give us hidayah till we can straighten our steps in implementing of Syariah Islam.